A total systems design study on Bristol Shoes - Baladiang, Angel Lou M.; Beltran, Christine Joyce D.; Catulong, Austin Dionne L.
Bristol Shoes is a Marikina-based Filipino retail and manufacturing organization specializing in men's footwear. It has been in the industry for almost 3 decades, now presently owned and managed by the 2nd and 3rd generation of the De Dios family. It employs almost 70 employees with its (2) tow manufacturing plants in Marikina and Antipolo. Recent industry data for Philippine retail footwear suggests that the demand for men's shoes will rapidly increase from 207-2022 by 22.7%. With the aim to meet this forecasted sales, Bristol's eyes a new production target rate of 180 pairs daily. This translates to a 50% increase from its current production rate. Some solutions implemented by the organization ws to implement a daily overtime for the upper-making production, and to set-up and additional production site in Antipolo. However, both solutions proved to be futile as the number of pairs produced did not improve. Moreover, the organization also faces uncertainty with its leather skins as their leather suppliers have a highly variable lead time. Current leather skin inventory management are said to be arbitrary. To be able to accommodate this expansion in production rate, (3) three productivity improvements were designed and simulated. An inventory management system considering lead time of suppliers, amount to order, and reorder points are calculated to lessen the frequency of stock outs. Next, a linear programming model is formulated to determine the optimal pairs of production. Through this model, it is discovered that their maximum capacity is at 120 pairs daily. This maximum capacity is mainly constrained by number of available shoe lasts. Additionally, job sequencing design is made to schedule a batch of production order which employs a bimonthly quota-based production. Implementation of the said improvements are designed to be in two (2) phases. The first phase will be to gradually increase from the current 90 pairs to the proposed 120 pairs daily. Once the company is able to acquire the needed amount of shoe lasts, Bristol may shift from phase 1 to phase 2 achieving the production goal of 180 pairs. However, significant dissemination and preparation of Bristol employees should be made in order for them to keep up with the production increase. Simulation results show that reaching phase 1 will guarantee a 23.59% improvement based from the identified KPIs. However, if the company is able to successfully implement until phase 2, a 58.84% improvement from the current will be achieved. A benefit-cost ratio of 4.07 will also be realized for the said implementation, which means that investments will be recovered from the increased sales of shoes.